Serat Suluk Siral Ustad: Kajian Filologis - Widodo (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
This study examines five manuscripts of Serat Suluk Sirul Ustad taken from the Radyapustaka Library, Reksapustaka Library of Pura Mangkunegaran, Sanapustaka Library of Surakarta Palace, and Sanabudaya Library of Yogyakarta. This research aims to examine the content or teachings contained therein. The collection of manuscripts from several places aims to obtain a genuinely original text of Serat Suluk Siral Ustad. The research method used in this study is adjusted to the methods and steps of philological work: manuscript inventory, manuscript description, manuscript comparison, and the basics of determining the manuscript to be transliterated, manuscript transliteration, translation, and text criticism. The text criticism method used is the grounding method and continued by analyzing the manuscript's content. This research uses descriptive analysis techniques to analyze the content of Serat Suluk Sirul Ustad. Serat Suluk Sirul Ustad contains things that need to be considered by someone looking for a teacher and knowledge to avoid being misled in this world and in the hereafter. In detail, Serat Suluk Sirul Ustad contains the virtues of seeking teachers and knowledge as much as possible, which later in Serat Suluk Sirul Ustad is called the primary teacher and the misguided teacher. In addition, Serat Suluk Sirul Ustad also contains advice on being careful in choosing teachers and knowledge, as well as the concept of a true teacher. The mystical teachings in Serat Suluk Sirul Ustad include the teachings of purification of the heart and meditation. The influence of Sufism in this text can be seen in the use of Arabic terms or words such as kharaam, makruh, sariat, jayin nafsaka, bilmaksiyati, and others, as well as the concept of servant unity with God or manunggaling kawula lan Gusti. The peak of realization in Serat Suluk Sirul Ustad adheres to the ahlus-sunah school of Sufism. There is still a difference between the servant and God in the unity between the servant and God.